WORK LOAD SHARING USING MOBILE EDGE COMPUTING - Arulprakash, M.; Mathur, Vibhor; Katoch, Arya; Katoch, Arya (International Journal of Psychosocial Rehabilitation, 2020)
Recently, intense use of mobile devices is increased and day by day new technology in communication is increasing so we have to accommodate more and more devices on the cloud server also we have to provide advanced algorithm for efficient exchange of resources between cloud and client server. Mobile devices users are saturated with already proposed traditional methods such as grid-computing. Our aim in this project is to reduce the load on mobile devices and reduces the work sharing in cloud environment. This paper supports the use of more optimum algorithm for mobile Edge-Clouds. In using mobile edge computing technology, we have a cellular operator that allows efficient deployment services for specific customers or classes of customers. This technology also reduces the signal load of the core network, and can host applications and provide services in a cheaper way. Data Sharing will increase traffic on mobile edge cloud to reduce it is our major aim of the project. Our idea is to secure and reliable data sharing in mobile edge cloud environment.To achieve this we are going to implement an Algorithm of BackScatter and Priority based task Sharing Algorithm.